KONSEP PERANCANGAN FASAD BANGUNAN BERDASARKAN KARAKTER FASAD BANGUNAN DALEM DI JALAN MONDORAKAN KOTAGEDE, YOGYAKARTA - Putra, Augustinus Madyana; Wibowo, Andi Prasetiyo (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: The uniqueness of an area is a soul place that will distinguish a location from another location. The historic Kotagede area of Yogyakarta is divided into four road sections, and one of the road sections is the Mondorakan Road. The building on Mondorakan Road originally consisted of a series of palace buildings with a very distinctive facade appearance with three types of building facades. After the earthquake that occurred in 2006, many buildings in this area were destroyed and renovated but did not adjust to the appearance of the original facade, so the uniqueness of the city became blurred. Through this research, it is expected to be able to identify and provide solutions to these conditions. The methods applied are case studies and observations in the field, then analyzed based on previous findings regarding three types of facade displays. The results of the analysis produce outcomes in the form of guidelines in the design process that are expected to be able to maintain the characteristics of an area. Facade reading is an important thing to keep because it can help preserve the soul of a place in this part of the road.Keyword: palace buildings, facade, the soul of a placeAbstrak: Keunikan sebuah kawasan merupakan sebuah jiwa tempat yang akan membedakan suatu lokasi dengan lokasi lain. Kawasan bersejarah Kotagede Yogyakarta terbagi menjadi 4 penggal jalan, dan salah satu penggal jalan tersebut yaitu Jalan Mondorakan. Bangunan di Jalan Mondorakan pada mulanya terdiri dari jajaran bangunan dalem dengan tampilan fasad yang sangat khas dengan tiga tipe fasad bangunan. Pasca gempa yang terjadi tahun 2006, banyak bangunan di area ini yang hancur dan direnovasi namun tidak menyesuaikan dengan tampilan fasad semula, sehingga keunikan kawasan menjadi kabur. Melalui penelitian ini diharapkan mampu mengidentifikasi dan memberi solusi mengenai kondisi tersebut. Metode yang diterapkan yaitu studi kasus dan observasi di lapangan, kemudian dianalisis berdasar temuan sebelumnya mengenai 3 tipe tampilan fasad. Hasil analisis menghasilkan temuan berupa panduan dalam proses perancangan yang diharapkan mampu mempertahankan ciri khas suatu kawasan. Keterbacaan fasad ini menjadi hal penting untuk tetap dipertahankan karena dapat membantu adanya jiwa tempat di penggal jalan ini.Kata Kunci: bangunan dalem, fasad, jiwa tempat